2009
DOI: 10.1186/1471-2164-10-579
|View full text |Cite
|
Sign up to set email alerts
|

A microarray analysis of sex- and gonad-biased gene expression in the zebrafish: Evidence for masculinization of the transcriptome

Abstract: BackgroundIn many taxa, males and females are very distinct phenotypically, and these differences often reflect divergent selective pressures acting on the sexes. Phenotypic sexual dimorphism almost certainly reflects differing patterns of gene expression between the sexes, and microarray studies have documented widespread sexually dimorphic gene expression. Although the evolutionary significance of sexual dimorphism in gene expression remains unresolved, these studies have led to the formulation of a hypothes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
82
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(103 citation statements)
references
References 59 publications
(100 reference statements)
20
82
1
Order By: Relevance
“…These differences were not due to temperature but to sex, and represent a substantial proportion of protein-coding genes in zebrafish (43). This concurs with previous observations (44)(45)(46) showing large sex-related differences in the gonadal transcriptome of the adult zebrafish.…”
Section: Transcriptomic Analysis Of Adult Zebrafish Gonads Revealed Asupporting
confidence: 92%
“…These differences were not due to temperature but to sex, and represent a substantial proportion of protein-coding genes in zebrafish (43). This concurs with previous observations (44)(45)(46) showing large sex-related differences in the gonadal transcriptome of the adult zebrafish.…”
Section: Transcriptomic Analysis Of Adult Zebrafish Gonads Revealed Asupporting
confidence: 92%
“…Some microarray-based studies on sex-specific gene expression patterns showed an important masculinization of the transcriptome (Small, et al, 2009). In Drosophila melanogaster recent works have shown that sex-biased gene expression is significant in Drosophila, especially in gonads.…”
Section: Discussionmentioning
confidence: 99%
“…Most of these studies have been focused in a few genes, being Dmrt1 the most analyzed because it is the only known non-mammalian vertebrate master sex-determining gene (Matsuda et al, 2002;Nanda et al, 2002). Large-scale gene expression studies have been made in a few fish species including zebrafish (Small et al, 2009), medaka (Lo et al, 2008), perch (Rossi et al, 2007), sea bass (Chini et al, 2006;Kulh et al, 2010), blue fin tuna (Chini et al, 2008) and three spine sticklebacks (Leder et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…For example, in mice, patterns of sex-biased gene expression vary between different tissues (Rinn et al 2004;Yang et al 2006). In zebrafish, Danio rerio, sex bias in the transcriptome of the brain tissue was found to be quite low ( 2%) (Santos et al 2008), but a different study identified sex biases across 38% of the transcriptome that were attributed to differences in gene expression in male and female reproductive tissues (Small et al 2009). Similarly, in the silkworm Bombyx mori, sex-biased gene expression varied between 2% and 30%, depending on the tissue examined (Xia et al 2007).…”
Section: Quantifying Sex-biased Gene Expressionmentioning
confidence: 99%